Comparison Of Median Nerve Conduction Velocity Between Player Games (Gamers) And Non-Player Games Based On Electroneuromyography - Ilsa Hunaifi; Herpan Syafii Harahap; Muhammad Galvan Sahidu; Triana Dyah Cahyawati (Fakultas Kedokteran UPN Veteran Jakarta Kerja Sama KNPT, 2021)
Playing games for a long period can induce a negative effect on the hands, especially on the median nerve. This study aims to compare median nerve conduction between gamers and non-gamers. This study was analyzed with a cross-sectional method of 40 subjects at University Mataram Hospital from September to October 2020. The subjects included gamers and non-gamers subjects as controls. All groups were tested the median nerve conduction velocity using Electromyoneurography. Demographic data were analyzed with descriptive and compare median nerve conduction study between two groups with the Mann Whitney test. Each group obtained 20 subjects. The mean median motor nerve conduction velocity on the right side of gamers and non-gamers is 2.83 ± 1.2 ms and 2.44 ± 1.2 ms, while the left side is 2.9 ± 1.0 ms and 2.5 ± 1.1 ms. The mean sensory median nerve conduction velocity on the right side of gamers and non-gamers is 2.31 ± 1.02 ms and 2.25 ± 0.88 ms, and the left side is 2.4 ± 1.1 ms and 2.25 ± 0.9 ms. The Mann-Whitney test showed no significant difference between the two groups (p>0.05).